Twelve tips to improve medical teaching rounds. (November 2013) - Abdool, Muhammad Ali; Bradley, Don
<x xml:space="preserve">Abstract</x> The ward round is the bread and butter of internal medicine. It forms the basis of clinical decision making and reviewing patients' progress. It is fundamental to the role of the internal medical physician. It allows for the review of the patients' notes, signs and symptoms, physiological parameters and investigation results. Most importantly, it allows for an interaction with the patient and their relatives and is a means of relating medical information back, answer queries and plan future medical management strategies. These should be integrated into the teaching round by a senior clinician so that time away from the bedside is also used to enhance the teaching and learning experience. Here, I would like to draw on my experience as a learner as well as an educator, together with the available literature, to draw up a simple 12-step teaching strategy that should help the ward round serve the dual purpose of teaching medical students and junior doctors.